1996
DOI: 10.1097/00004647-199601000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Short Therapeutic Window for MK-801 in Transient Focal Cerebral Ischemia in Normotensive Rats

Abstract: The present study investigates the role of N-methyl-D-aspartate (NMDA) receptors in a model of transient focal cerebral ischemia in normotensive rats. The left middle cerebral artery and both common carotid arteries were occluded for 60 min. Preliminary studies indicated that this gave reproducible infarctions of the cortex and striatum. These infarctions were the result of severe ischemia followed by complete reperfusion after clamp removal, as showed by striatal tissue Po2 monitoring. Microdialysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 27 publications
5
39
0
Order By: Relevance
“…8 B) (Loschmann et al, 2004) 3 h after a 1.5 h MCAo challenge (4.5 h after stroke onset) did not provide any noticeable neuroprotection when compared with MCAo alone (Fig. 8 A), which was in line with previous reports (Xue et al, 1994;Margaill et al, 1996). In contrast, selective activation of synaptic NMDA receptors, which are predominantly NR2A-containing receptors, with the application of NMDA receptor coagonist glycine [800 mg/kg (De et al, 2000)] resulted in a remarkable reduction in total infarct volume (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…8 B) (Loschmann et al, 2004) 3 h after a 1.5 h MCAo challenge (4.5 h after stroke onset) did not provide any noticeable neuroprotection when compared with MCAo alone (Fig. 8 A), which was in line with previous reports (Xue et al, 1994;Margaill et al, 1996). In contrast, selective activation of synaptic NMDA receptors, which are predominantly NR2A-containing receptors, with the application of NMDA receptor coagonist glycine [800 mg/kg (De et al, 2000)] resulted in a remarkable reduction in total infarct volume (Fig.…”
Section: Resultssupporting
confidence: 91%
“…As expected, we found that treatment with either nonsubunit-specific NMDA receptor antagonist MK-801 (1 mg/kg) (Fig. 8 A) (Margaill et al, 1996) or NR2B-specific antagonist Ro 25-6981 (6 mg/kg) (Fig. 8 B) (Loschmann et al, 2004) 3 h after a 1.5 h MCAo challenge (4.5 h after stroke onset) did not provide any noticeable neuroprotection when compared with MCAo alone (Fig.…”
Section: Resultssupporting
confidence: 77%
“…The N-methyl-D-aspartate (NMDA) receptor blocker MK-801 markedly reduces ischemic brain injury; however, MK-801 has a brief therapeutic time window: the neuroprotective effect of MK-801 is obtained only when therapy is given within at most 1 hour after the onset of focal ischemia in rats and gerbils. 2,3 Furthermore, MK-801 only postpones postischemic neuronal death; it does not improve either neurological recovery or endpoint cell survival at weeks after treatment. 4,5 Similarly, ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor antagonists also did not significantly protect neuronal loss at 28 days after middle cerebral artery occlusion (MCAO).…”
mentioning
confidence: 99%
“…In the adult rat, NMDA antagonists have been shown to decrease infarct volume after transient MCAO when administered just before ischemic (Margaill et al, 1996). Antioxidants such as NXY-059, ebselen, and edaravone appeared to extend the P <0.01 P < 0.01 P <0.05 Note the punctate pattern of neuronal mitochondrial free radical (yellow), which is increased in the ischemic penumbral areas.…”
Section: Enhanced and Extended Neuroprotection Against Transient Focamentioning
confidence: 99%